PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PENINGKATAN KECERDASAN SPIRITUAL PESERTA DIDIK - Hasanah, Annisa; Anwar, Saeful; Munggaran, Nita Anjung (THORIQOTUNA: Jurnal Pendidikan Islam, 2021)
The study aims to determine the effect of learning education Islam in the middle of the Islamic Islam Serba Bakti Suryalaya. Methods used in this study is the descrivtive through a quantitative approach is research trying to reveal the state of or conditions that happened while now to consider the state of the past trought of processing numbers derived from the research. Based on the results of treatment data obtained that the influence of learning education Islam against an increase in intelligence spiritual learners in the middle of the influence of Islamic Islam Serba Bakti Suryalaya to have a significant positive with the category of enough, proved rs = 0,59 interval 0,41 – 0,60 serta t hitung (3,226) t tabel (1,725). earning education islam determine increasing spiritual learners by 35%, while the rest 65% believed to be determined by other factors.